Politeness Strategies of the Main Characters of Pride and Prejudice Movie - Luluatul Musyafa'ah; Issy Yuliasri; Hendi Pratama (English Education Journal, 2022)
In conversations, people tend to speak politely to keep their interlocutors’ feelings so the conversation can be maintained in harmony. They follow several rules and principles that already exist in society. They apply politeness strategies so that the communication can run effectively. This study aims to discover the politeness strategies performed by the main characters of Pride and Prejudice movie and explain the pattern of different types of strategies used in the movie. The data were taken from the movie’s transcript as the primary source. A descriptive qualitative method was used to analyze politeness strategies proposed by Brown and Levinson. Based on the analysis, the politeness strategies were used by the main characters of Pride and Prejudice movie. The types of politeness strategies employed are bald-on record, positive politeness, negative politeness, and off-record strategy. The most frequent strategy was positive politeness which occurred 98 times from 149 data. The patterns of politeness strategies applied are in declarative, interrogative, imperative, and exclamatory sentences. All types of sentences contain bald-on record, positive politeness, negative politeness, and off-record strategies. By using politeness strategies, people appreciate their interlocutors so that the conversation will be well-maintained. Besides, this study contributes to English language teaching in comprehending cross-cultural understanding (CCU) through the movie, especially in western culture.